2022
DOI: 10.1021/acs.jafc.2c03025
|View full text |Cite
|
Sign up to set email alerts
|

mTOR-Mediated Autophagy Regulates Fumonisin B1-Induced Intestinal Inflammation via Pyroptosis In Vivo and In Vitro

Abstract: Fumonisin B 1 (FB 1 ) is a fungal metabolite, which has an incremental detection rate in grains and feed worldwide. The nucleotide-binding oligomerization domain-like pyrin domain containing protein 3 (NLRP3) inflammasome is a critical element in pyroptosis activation, which participates in regulating enteritis. Meanwhile, autophagy is also engaged in intestinal inflammation. However, the function of pyroptosis and autophagy in FB 1 -mediated enterotoxicity remains unclear. In this study, we explored the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…32 Li et al found that FB1 induced intestinal epithelial barrier injury via endoplasmic reticulum stress. 33 via pyroptosis and mTOR-mediated autophagy was discovered by Mao et al 34 According to earlier study, FB1 has a considerable impact on the gut microbiota and the relative abundance of bacteria at the phylum to species level, with Firmicutes and Proteobacteria being the two major groups that are differentially affected. 21 In addition, fumonisin exposure has caused serious harm to humans and animals, resulting in significant economic losses.…”
Section: Discussionmentioning
confidence: 98%
“…32 Li et al found that FB1 induced intestinal epithelial barrier injury via endoplasmic reticulum stress. 33 via pyroptosis and mTOR-mediated autophagy was discovered by Mao et al 34 According to earlier study, FB1 has a considerable impact on the gut microbiota and the relative abundance of bacteria at the phylum to species level, with Firmicutes and Proteobacteria being the two major groups that are differentially affected. 21 In addition, fumonisin exposure has caused serious harm to humans and animals, resulting in significant economic losses.…”
Section: Discussionmentioning
confidence: 98%
“…After collecting the intestinal tissue samples, pathological tissue sections were made (H&E). For the details see Mao et al (Mao et al 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…After FB1 treatment, cells were washed twice with pre-cooled PBS. Then, the qRT-PCR detail steps were reported in our previous study (Mao et al 2022 ). The primers used are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2020) demonstrated that DON activates autophagy in IPEC‐J2 cells by disrupting the Phosphoinositide 3 kinase (PI3K)–Protein Kinase B (Akt)–mTOR signaling pathway, resulting in cytotoxicity and apoptosis. Both in vivo and in vitro experiments have provided substantial evidence that FB 1 exposure triggers mTOR‐mediated autophagy, promoting intestinal cell charring and inflammation (Mao et al., 2022). Additionally, OTA exposure has been found to activate autophagy in IPEC‐J2 cells through the Extracellular regulated protein kinases 1/2 (ERK1/2) cascade (Wang, Li, Chen, et al., 2018).…”
Section: The Intestinal Toxicity Mechanism Of Foodborne Mycotoxinsmentioning
confidence: 99%